Genomic reconnaissance of clinical isolates of emerging human pathogen Mycobacterium abscessus reveals high evolutionary potential - Choo, S.W.; Wee, W.Y.; Ngeow, Y.F.; Mitchell, W.; Tan, J.L.; Wong, G.J.; Zhao, Y.; Xiao, J. (2014)
Mycobacterium abscessus (Ma) is an emerging human pathogen that causes both soft tissue infections and systemic disease. We present the first comparative whole-genome study of Ma strains isolated from patients of wide geographical origin. We found a high proportion of accessory strain-specific genes indicating an open, non-conservative pan-genome structure, and clear evidence of rapid phage-mediated evolution. Although we found fewer virulence factors in Ma compared to M. tuberculosis, our data indicated that Ma evolves rapidly and therefore should be monitored closely for the acquisition of more pathogenic traits. This comparative study provides a better understanding of Ma and forms the basis for future functional work on this important pathogen.